Attitudes towards breastfeeding associated with exclusive breastfeeding practice in Mexican mothers - Jiménez Medina, Luis Angel (2023)
Objective: Determine the association between attitudes towards breastfeeding and the practice of exclusive breastfeeding in Mexican mothers. Material and method: The study design was descriptive, correlational and cross-sectional. The sample was 169 mothers. Biological mothers with at least one child from 0 to 24 months of age and with signed informed consent were included. We used a sociodemographic data card, the Scale of Attitudes towards Infant Feeding and questions about the practice of breastfeeding. We calculated univariate and bivariate descriptive statistics. Results: The sample of this study involved 169 dyads (mother and son). The mean age of the mothers was 27,22 (SD = 5,70) years.  According to attitudes towards feeding, 59,80% reported a neutral attitude towards infant feeding. 52,10% of mothers reported that they would stop breastfeeding after 12 months of age. 83,10% of mothers give exclusive breast milk to their child under 6 months of birth. A weak significant association was found between attitudes towards breastfeeding associated with age in months of abandoning exclusive breastfeeding (X2 (2, 169) = 11,40, p<0,022). Conclusions: The mothers reported that their children received breast milk in the first hour of birth, although the frequency decreased as the child grew. There was an association between positive attitudes towards breastfeeding with breastfeeding practice in the first six months after birth.